Activation of EGFR‐KLF4 positive feedback loop results in acquired resistance to sorafenib in hepatocellular carcinoma. Issue 11 (29th August 2019) - Pang, Lijun; Xu, Lin; Yuan, Chunwang; Li, Xiuhui; Zhang, Xiangying; Wang, Wenjing; Guo, Xianghua; Ouyang, Yabo; Qiao, Luxin; Wang, Zhenchang; Liu, Kai
Abstract: Sorafenib is the standard first‐line systemic chemotherapeutic drugs for advanced hepatocellular carcinoma (HCC), but acquired resistance to sorafenib is frequently observed in clinical practice. In this study, we first produced three sorafenib resistance (SR) HCC cell lines by using two human HCC cell lines (Hep3B and Huh7) and a human primary HCC cell line. We identified that epidermal growth factor receptor (EGFR) and Kruppel‐like factor 4 (KLF4) are dramatically increased in the three SR HCC cell lines. Either inhibition of tyrosine kinase activity of EGFR with Erlotinib/Icotinib or inhibition of KLF4 expression with short hairpin RNA recovered the response of three SR HCC cell lines to sorafenib, suggesting the critical roles of EGFR tyrosine kinase and KLF4 on inducing SR. Luciferase activity and chromatin immunoprecipitation assays further determined that KLF4 promoted EGFR expression through inducing its transcription by directly binding to its promoter. EGFR, conversely, could also promote KLF4 expression through inducing its transcription by binding to its promoter in a tyrosine kinase‐dependent manner, suggesting that a positive feedback loop formed by EGFR and KLF4 further amplifies their effects on inducing SR. Up to now, our findings that KLF4 induces the development of SR and it cooperates with EGFR to form a positive feedback loop to amplify their SR‐inducing abilities have rarely been reported. Our findings bear possible implications for the improvement of the efficacy of sorafenib in HCC.